London presbyterians and the British revolutions, 1638-64 - Vernon, Elliot, 1972- (Politics, Culture and Society in Early Modern Britain Series., 2021)
London presbyterians and the British revolutions is a case study in the politics of metropolitan religion and presbyterianism in the middle decades of the seventeenth-century.